Symposium on non-destructive testing of concrete and timber (Institution of Civil Engineers, 1970)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium organized with the British National Committee for Non-destructive Testing held on 11-12 June 1969.